PERTANGGUNGJAWABAN WAKIL PRESIDEN MENURUT SISTEM PEMERINTAHAN INDONESIA (STUDI PERTANGGUNGJAWABAN WAKIL PRESIDEN PASCA PERUBAHAN UUD 1945) - Ansori, Lutfil (Jurnal Yuridis, 2014)
In the system of government of the Republic of Indonesia, the President holds the highest governmental authority in carrying out its obligations assisted by a Vice President. The 1945 Constitution of the Republic of Indonesia, article 4 is said "In performing duties, the President is assisted by a Vice President". Constitutionally this article shows the position and duties of the Vice President as assistant to the President. Presenting the system of government by the constitution is intended to determine a position of the Vice President in related with the President in terms of responsibility. Based on normative juridical approach in this research, it is concluded that the presence of 1945 Constitution Amendment increasingly clarifies that the Vice President responsibility is to the President. It is based on the position of the Vice President interpretation in the Indonesian system that is not equal. This unequal position shows that the presidency as an organizer of the government administration is singular (single executive). However, to avoid the impression of the Vice President as a "spare tire", the Vice President should be given a clear constitutionally duties by delegating or sharing ofduties and not through delegating or sharing of the power